PENGARUH PROPORSI TEPUNG IKAN DAN TEPUNGKEONG MAS (Pomacea canaliculata) YANG BERBEDA SEBAGAI BAHAN BAKU UTAMA PEMBUATAN PAKAN TERHADAP PERTUMBUHAN BENIH UDANG VANNAMEI (Litopenaeus vannamei) - Tari Putri Anggraini; Siti Hudaidah; Deny Sapto Chondro Utomo (e-Jurnal Rekayasa dan Teknologi Budidaya Perairan, 2018)
Feed is the main source of nutrients to support vannamei shrimp growth. The high cost of feed in operational costs due to the high raw material price of fish meal, limited availability, while the demand is high. Therefore it is necessary to find alternative materials that are low in price, have a high enough protein content and abundant availability such as golden snail flour. The purpose of this study was to analyze the effect of different proportion of fish meal and mashed snail (Pomacea canaliculata) as the main feedstock for the growth of shrimp vannamei (Litopenaeus vannamei). The experimental design used in this study was Completely Randomized Design (RAL) consisting of 5 treatments, namely A (57.18% use of fish meal in feed), B (42.89% use of fish meal, 14.30% mashed flour), C (28.59% fish meal usage, 28.59% mashed snail), D (Use of 14.30% fish meal, 42.89% mashed snail), and E (Use 57.18% golden snail flours). This study shows that the addition of mashed snail flour in the feed can increase the growth of absolute weight, the daily weight of vannamei shrimp, and can decrease the value of FCR.